2011
DOI: 10.1111/j.1462-2920.2011.02664.x
|View full text |Cite
|
Sign up to set email alerts
|

Sponge‐specific clusters revisited: a comprehensive phylogeny of sponge‐associated microorganisms

Abstract: Marine sponges often contain diverse and abundant communities of microorganisms including bacteria, archaea and eukaryotic microbes. Numerous 16S rRNA-based studies have identified putative 'sponge-specific' microbes that are apparently absent from seawater and other (non-sponge) marine habitats. With more than 7500 sponge-derived rRNA sequences (from clone, isolate and denaturing gradient gel electrophoresis data) now publicly available, we sought to determine whether the current notion of sponge-specific seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
374
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(390 citation statements)
references
References 36 publications
15
374
1
Order By: Relevance
“…In addition, the ascidian microbiota demonstrated some overlap with other host-associated microbial communities yet clear distinction from ambient planktonic communities in coral reef seawater, except for the widespread presence of Cyanobacteria from the Prochlorococcus genus. Consistently, previous studies have noted multiple shared symbiont lineages among microbiota of sponges and corals (Taylor et al, 2007;Simister et al, 2012), indicating microbial lineages adapted to host-associated lifestyles may disperse among disparate host organisms. However, the ascidian microbiota also maintained distinguishing characteristics in comparison to other host-associated communities.…”
Section: Discussionsupporting
confidence: 65%
“…In addition, the ascidian microbiota demonstrated some overlap with other host-associated microbial communities yet clear distinction from ambient planktonic communities in coral reef seawater, except for the widespread presence of Cyanobacteria from the Prochlorococcus genus. Consistently, previous studies have noted multiple shared symbiont lineages among microbiota of sponges and corals (Taylor et al, 2007;Simister et al, 2012), indicating microbial lineages adapted to host-associated lifestyles may disperse among disparate host organisms. However, the ascidian microbiota also maintained distinguishing characteristics in comparison to other host-associated communities.…”
Section: Discussionsupporting
confidence: 65%
“…are nitrite oxidizers and are proposed to have key roles in nitrogen fixing and cycling within the ascidian tunics Lucker et al, 2013). Another group that was slightly enriched in L. badium samples specifically in PNG_11062 (22%) is the Acidimicrobiales class of actinobacteria, a group that was previously described as a sponge-specific bacterial group (Simister et al, 2012). All the analyses for identifying the most abundant species-specific bacteria were further confirmed by Metastats analyses for the statistical identification of differentially abundance OTUs (data not shown).…”
Section: Bacterial Composition Of Ascidiansmentioning
confidence: 99%
“…Numerous studies have reported the existence of monophyletic sponge-specific 16S ribosomal RNA (rRNA) gene sequence clusters, representing bacteria found in sponges but not detected in other environments, such as seawater (Hentschel et al, 2002;Taylor et al, 2007;Simister et al, 2012). In a recent 16S rRNA gene tag pyrosequencing study (Webster et al, 2010), we revealed the presence of sequences affiliated with 'sponge-specific' clusters in seawater.…”
mentioning
confidence: 99%
“…The analysed data demonstrate the power of next-generation sequencing technologies Figure 2 Occurrence of 'sponge-specific' 16S rRNA gene sequence clusters in ICoMM samples. Heatmap showing the distribution of representatives of previously described 'sponge-specific' 16S rRNA gene sequence clusters (Simister et al, 2012) among the V6 pyrotag sequences downloaded from the ICoMM website. Clusters with an SC prefix contain sequences previously reported only from sponges; SCC prefix signifies clusters containing only sponge-and coral-derived sequences.…”
mentioning
confidence: 99%
See 1 more Smart Citation